Evaluation of Zero-Energy Building and Use of Renewable Energy in Renovated Buildings: A Case Study in Japan - Ryoichi Kuwahara; Hyuntae Kim; Hideki Sato (Buildings, 2022)
Following the Paris Agreement in 2015, the worldwide focus on global warming countermeasures has intensified. The Japanese government has declared its aim at achieving carbon neutrality by 2050. The concept of zero-energy buildings (ZEBs) is based on measures to reduce energy consumption in buildings, the prospects of which are gradually increasing. This study investigated the annual primary energy consumption; as well as evaluated, renewed, and renovated buildings that had a solar power generation system, and utilized solar and geothermal heat. It further examines the prospects of hydrogen production from on-site surplus electricity and the use of hydrogen fuel cells. A considerable difference was observed between the actual energy consumption (213 MJ/m2), and the energy consumption estimated using an energy simulation program (386 MJ/m2). Considerable savings of energy were achieved when evaluated based on the actual annual primary energy consumption of a building. The building attained a near net zero-energy consumption considering the power generated from the photovoltaic system. The study showed potential energy savings in the building by producing hydrogen, using surplus electricity from on-site power generation, and introducing hydrogen fuel cells. It is projected that a building’s energy consumption will be lowered by employing the electricity generated by the hydrogen fuel cell for standby power, water heating, and regenerating heat from the desiccant system.